(untitled) - UNFPA Vietnam (Hà Nội, 2011)
This profile of key sex-disaggregated indicators from the 2009 Viet Nam Population and Housing Census is an initial effort to extract fundamental information on gender differences based on census indicators, and thereby to identify areas (both sectoral and geographic) where gender gaps still remain. It is thus an attempt to supplement existing information and evidence on gender equality in Viet Nam and is intended to demonstrate the importance of a systematic sex disaggregation in data analysis for evidence-based and effective policy development and planning. This booklet represents the seventh in a series of booklets published by UNFPA in recent years. It is based solely on the Population and Housing Census data, particularly the 15% sample of 2009 and the 3% sample data of 1999, and draws from the Major Findings1 and a series of census monographs developed by the GSO and UNFPA.
Keywords: Tỷ lệ giới tính,Nam và nữ; Men and women,Sex ratio; Vietnam,Vietnam,Việt Nam,Việt Nam